(untitled) (Revista LIDER, 2018)
This study analyzes changes in the patterns of motility in the Inner Sea of Chiloé, Region of the Lakes, in relation to identity, the normative and educational conditions that influence the freedom of being and being and doing, based on insular culture itself.